A Study on Energy Consumption of a Resort Located in the East Coast of Malaysia - M. R. R., Chand; F., Basrawi; Hassan, Ibrahim; Mohd Yusof, Taib; Afzam, Zulkepli (IASE, 2016)
Rapid developments on tourism industry in Malaysian east coastal areas are expected to increase the electricity consumption. The situation worsens as the intermittent weather condition in that area also causes inconstancy on the electrical consumptions pattern. Thus conducting studies on electricity consumption are essential to ensure reliable and economic power generation in future. This paper intends to elaborate on the study conducted to estimate hourly energy consumption of a resort complex consisting of 34 chalets and a restaurant. A survey was performed to obtain variables such as number of occupants, chalets occupancy, chalets building material, restaurant operations as well as typical daily electricity consumption. The electrical energy consumption was evaluated in three different end- use categories namely air conditioning, domestic water heating and electrical appliances for both chalets and restaurant. Various estimation methods were implemented in order to segregate the energy consumption into respective end use group. The results show that the average electricity consumption from November to January is lower compared to consumption in March to October due to monsoon season. Furthermore, 40% of electricity consumption was contributed by air conditioning usage in the chalets.